PENGARUH EKSTRAK DAUN KEMBANG BULAN (Tithonia diversifolia A.Gray) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH WISTAR YANG DIINDUKSI OLEH ALOXAN - Pradiningsih, Anna; Pandanwangi Tw, Siti; Aribowo, Aribowo (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Diabetes mellitus becomes a major health problem because its complications are short and long term. Plants used for the treatment of diabetes, one of which is Daun Kembang Bulan (Tithonia diversifolia A.Gray). Daun Kembang Bulan (Tithonia diversifolia A.Gray) is used as an anti-diabetic with the active substance of sesquiterpene compound, 1?-hydroxydiversifolin-3-O-methyl ether and 1?-hydroxytirotundine-3-O-methyl ether, isolated from the aerial part-all parts of the plant except root of Kembang Bulan (Tithonia diversifolia A.Gray) Objective: To find out whether the Daun Kembang Bulan (Tithonia diversifolia A.Gray) had an effect on aloxan-induced glucose levels of rats, knowing which doses were more effective had a decreasing effect on rat glucose and on the stability of the leaf-bloom formulation of Daun Kembang Bulan (Tithonia diversifolia A.Gray) Method: The research method used is experimental method. The extract suspension was prepared with three doses, 200 mg/kgBB , 300 mg/kgBB, dan 400 mg/kgBB performed on 15 male rats induced aloxan. Result: Based on the result of measurement of the decrease of blood glucose level on male white rats after 21 days treatment can be seen that the suspension of Daun Kembang Bulan (Tithonia diversifolia A.Gray) extract at dose 200 mg/kgBB, 300 mg/kgBB, and 400 mg/kgBB obtained percentage decrease equal to 44%, 62.3% and 63.2%. On the Positive Control of Acarbose suspended with a dose of 9 mg/kgBB obtained percentage decrease of 57%. On Negative Control the 1% CMC suspension yields an increase percentage of 15.7%. The result of data analysis with T test test stated that there was no significant difference between the three doses with positive control. Conclusion: The effective dose is the dose with the lowest percentage of 200 mg/kgBB. The suspension stability of Daun Kembang Bulan (Tithonia diversifolia A.Gray) extract at doses of 200mg/kgBB, 300 mg/kgBB dan 400 mg/kgBB, positive control and negative control is relatively stable at temperatures of 0 0C, 25 0C and 50 0C.